ANALISIS PERFORMA RANCANG BANGUN SISTEM LIVE STREAMING MENGGUNAKAN SOFTWARE ENCODER VMIX - priyambudi, Rizal; Pinasthika, Stanislaus Jiwandana (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Abstract. Live streaming is a technology that allows the distribution of audio and video content in real-time over the internet. In this study, Quality of Service (QoS) performance testing will be conducted in the implementation of live streaming on Television broadcasting systems using Vmix encoder software. Testing is done by giving variations in bitrate values of 500 kbps, 750 kbps, 1000 kbps, and 1250 kbps during the video upload process to the server. Then, during the video content download process from the server, variations in the number of clients will be given with one, two, and three clients. The test results show that a bitrates of 1250 kbps provides the best QoS value with a delay of around 5.177 ms, jitter of 8.635 ms, packet loss of 0.422%, and throughput of 1429.206 kbit. For the download process test, two active clients provide the best QoS qualification with a delay value of 5.0988 ms, jitter of 8.639 ms, packet loss of 0.6022%, and throughput of 1604.9635 kbit.